Continuous Midwifery Care for Mrs. P at TPMB Karin Alesha, Subang Regency - Karim, Fatmawati; Arlym, Lisa Trina (Universitas Ibn Khaldun Bogor, 2024)
This final project report discusses the continuous midwifery care for Mrs. P at TPMB Karin Alesha by using the case study method using continuity of care. Case taking through the SOAP approach. Observation of Mrs. P shows that COC is carried out three visits during various phases of pregnancy and childbirth, as well as appropriate examinations during the postpartum and neonate periods. Midwifery care also includes complementary therapies such as warm compresses for discomfort during pregnancy. In the delivery phase, the use of gym ball and pelvic rocking therapy to overcome pain and accelerate the smooth delivery process. In addition, postpartum care is also carried out by providing appropriate care, including the application of oxytocin massage to facilitate breast milk production. As well as providing care to neonates. Through this Final Project Report, it is hoped that health workers at TPMB Karin Alesha can maintain and improve services in providing midwifery care during pregnancy, childbirth, BBL, postpartum, and family planning, to minimize the mortality rate and/or pain rate in mothers and babies.